Pushing ahead: Advancing collective bargaining rights in the library - Dekker, Jennifer (Université d'Ottawa | University of Ottawa, 2020)
Well-resourced libraries are core to advancing the goals of the academy and the work of faculty and students. Often overlooked due to their small numbers, what challenges do librarians and archivists face in the workplace and how can we ensure they are supported?
Keywords: Academic librarians; Archivists; Collective bargaining; Faculty associations